LITHUANIAN AND LATVIAN SOCIAL EDUCATORS’ OCCUPATIONAL STRESS AND THE ANALYSIS OF ITS COPING POSSIBILITIES: SOCIAL EDUCATORS’ EXPERIENCES - Orska, Rita; Alifanoviene, Daiva; Šapelytė, Odeta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Stress is a condition related to complaints or disturbances of physical, psychological or social nature, which occur, if an individual does not feel able to fulfil all the requirements and expectations. In order to cope with stress situations, a person makes a particular effort for the regulation of it, in other words, for coping (overcoming, self-control). The coping is a multidimensional construct. The studies on this construct are rather recent in science, are carried out in the last twenty years. Due to that, the focus in stress research has shifted. Currently, more studies are conducted on prevention problems, how to develop and find resources in personality to cope with stress effectively. The first results of the study on the stress management peculiarities of social educators are reviewed in this paper as well. The research aim: to disclose the context of manifestation of occupational stress experienced by Lithuanian and Latvian social educators and its coping possibilities.